2021
DOI: 10.1021/jacs.1c12118
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Dalesconol A by Pd(0)/Norbornene-Catalyzed Three-Fold Domino Reaction and Pd(II)-Catalyzed Trihydroxylation

Abstract: Herein, we describe a concise total synthesis of dalesconol A through a “polycyclization/oxidation” approach. In the polycyclization stage, a Pd(0)/NBE-catalyzed 3-fold domino reaction and a subsequent intramolecular Michael addition have been utilized for the one-step assembly of the heptacyclic molecular skeleton. In the late stage of oxidation state adjustments, a stepwise sequence including site-selective benzylic oxidation, Pd­(II)-catalyzed oxime ether directed trihydroxylation, and desaturation has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Luckily, the check with Co­(OAc) 2 ·4H 2 O/KBr/O 2 /PPh 3 /NHPI, a protocol from Zeng and co-workers, led to the formation of 4 in 33% yield. However, the desired oxidation cannot be observed under Luan’s condition, NHPI/CuCl/O 2 in PhCN . During our study on the NHPI-mediated benzylic aerobic oxidation of 20 , it was demonstrated that different cobalt salts and bromide salts had evident effects on this process .…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Luckily, the check with Co­(OAc) 2 ·4H 2 O/KBr/O 2 /PPh 3 /NHPI, a protocol from Zeng and co-workers, led to the formation of 4 in 33% yield. However, the desired oxidation cannot be observed under Luan’s condition, NHPI/CuCl/O 2 in PhCN . During our study on the NHPI-mediated benzylic aerobic oxidation of 20 , it was demonstrated that different cobalt salts and bromide salts had evident effects on this process .…”
mentioning
confidence: 81%
“…However, the desired oxidation cannot be observed under Luan's condition, NHPI/CuCl/O 2 in PhCN. 18 During our study on the NHPI-mediated benzylic aerobic oxidation of 20, it was demonstrated that different cobalt salts and bromide salts had evident effects on this process. 19 obtained as the minor product.…”
mentioning
confidence: 88%
“…Polycyclic aromatic hydrocarbons (PAHs) have attracted much attention due to their novel optoelectronic, self-assembly, and charge-transport properties resulting from their unique π-conjugated scaffold. Therefore, synthetic strategies to produce PAHs have been extensively explored. In 2015, the Wen group disclosed palladium-catalyzed insertion of internal alkynes into cyclic diaryliodoniums via [4 + 2] benzannulation to generate various phenanthrenes, one of the vital molecular structural features in functional materials .…”
Section: Synthetic Applications Of Cyclic Aryliodoniumsmentioning
confidence: 99%
“…In the past few decades, domino reactions under the catalysis of palladium complexes have made significant progress. Noteworthy among them is the Catellani reaction based on palladium/norbornene catalysis, serving as an efficient strategy to synthesize polysubstituted aromatics . Meanwhile, palladium-catalyzed domino reactions via a retro-Diels–Alder strategy have received intense attention in recent years.…”
Section: Introductionmentioning
confidence: 99%